Inorganic crystal material as well as preparation method and application thereof

By co-doping Nd3+ and Dy3+ ions in inorganic crystal materials, combined with high-temperature solid-phase sintering and melt lifting method, the problem of insufficient research on green light band laser materials was solved, and the 496nm green light band laser output was achieved under 448nm pump. Suitable for high-power lasers and industrial processing.

CN119287516AActive Publication Date: 2025-01-10FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411204395.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-10
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

There is a lack of research on glaucoma laser materials in the prior art, especially in the application of high-power glaucoma lasers and the research of ultraviolet lasers, which limits its further development in the field of biomedical medicine.

Method used

The Dy3+ activated inorganic crystal material NdxDyyLu3-x-yAl3ScGaO12 is used to use the Dy3+ co-doped Nd3+ sensitized ions, and the laser output of the ~496nm green light band is achieved through blue light LD pumping, and the Dy3+ and Nd3+ ions of different concentrations are distributed on the same lattice with O atoms. Connection, combining high-temperature solid phase sintering and melt lifting method to prepare single crystals.

Benefits of technology

It has achieved the production of 496nm green light band laser output under 448nm pump, meeting the needs of high-power all-solid-state lasers, and growing large-sized single crystals, which are suitable for industrial fields such as mechanical cold processing and photoengraving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287516A_ABST
    Figure CN119287516A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic crystal material as well as a preparation method and application thereof, and belongs to the field of inorganic optical function crystal materials. The chemical formula of the inorganic crystal material is Nd < x > Dy < y > Lu < 3-x-y > Al < 3 > Sc GaO < 12 >, wherein 0.002 < = x < = 0.005, 0.005 < = y < = 0.05, and 0.1 < = x / y < = 0.5; nd < 3 + > and Dy < 3 + > replace the lattice of Lu < 3 + > in the crystal and are jointly distributed on the same lattice. The invention also provides a preparation method of the inorganic crystal material, and a single crystal with the size of phi 30mm * (50-60) mm can be grown. The inorganic crystal material is used for realizing blue light band laser output, and can realize 496nm blue light band laser output under 448nm pumping. The inorganic crystal material is good in optical quality and can meet the requirements of a high-power all-solid-state laser.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to an inorganic crystal material and a preparation method and application thereof, belonging to the field of inorganic optical functional crystal materials. Background Art

[0002] Visible band all-solid-state lasers have broad application prospects in laser processing, storage, display, lithography technology, biomedicine and other fields. Compared with long-wavelength lasers, short-wavelength laser processing has its unique advantages. It performs "cold" processing by directly destroying the chemical bonds in the material without generating a large amount of waste heat. Therefore, it becomes an ideal tool for processing fragile materials such as plastic products. It can also be used for metal punching, cutting and marking, etc. Moreover, the laser has good focusing performance and high resolution, making it the most ideal laser light source for laser processing such as optical engraving, 3D printing, high-precision circuit boards, solar cells, LED conductive film processing, chip marking, and fine drilling.

[0003] In recent years, as people's research on LED lighting continues to deepen, the power of InGaN / GaN-based blue laser diodes has reached above the watt level, and the cost has continued to decrease, which has provided the possibility of directly pumping laser crystals to produce visible band lasers, bringing the research and application of visible band lasers into a new stage. Using blue light LD to directly pump laser crystals can directly obtain laser outputs such as cyan, yellow, red, and orange. This method has the advantages of low signal-to-noise ratio, high stability, and high beam quality. Therefore, direct pumping to achieve visible band lasers is currently the most convenient method and has been a hot research topic in the laser field in recent years.

[0004] Doping Tb into laser gain medium 3+ 、Sm 3+ 、Dy 3+ 、Eu 3+ and Pr 3+ Rare earth ions such as Pr 3+ Laser crystals can emit fluorescence in multiple wavelengths (blue, green, red and orange), and there are many reported studies. Currently, the crystals that have achieved yellow laser light include Dy 3+ The activated YAG and LiLuF4 crystals have excellent comprehensive performance and have become the most widely studied yellow laser crystal materials. However, research on cyan lasers is still relatively lacking, and there are few public reports. High-power cyan lasers are widely used in the biomedical field, and further, ultraviolet lasers can be achieved through cyan laser frequency doubling technology, and research in this field is still blank. In view of the current weak research foundation on cyan laser materials, further research on new cyan laser crystal materials has important scientific and practical value. Summary of the invention

[0005] The present application provides a co-doped Nd 3+ Sensitizing ion Dy 3+ Activated inorganic crystalline material, namely crystalline Nd x Dy y Lu 3-x-y Al3ScGaO 12 , where 0.002≤x≤0.005, 0.005≤y≤0.05, 0.1≤x / y≤0.5; where Nd 3 + 、Dy 3+ 、Lu 3+ Distributed together on the same lattice, connected with 8 O atoms to form a dodecahedron, Al 3+ Sc 3+ and Ga 3+ Distributed on the same lattice site, connected to O atoms in four-coordinate and eight-coordinate modes. Due to the disordered distribution of multiple ions on the same lattice site, the crystal field regulation effect and Nd 3+ 、Dy 3+ The sensitization mechanism between ions, based on this crystal, using blue light LD pumping can achieve ~496nm cyan band laser.

[0006] According to the first aspect of the present application, an inorganic crystalline material is provided, the chemical formula of the inorganic crystalline material is

[0007] Nd x Dy y Lu 3-x-y Al3ScGaO 12 ;

[0008] Among them, 0.002≤x≤0.005, 0.005≤y≤0.05, 0.1≤x / y≤0.5;

[0009] Nd 3+ 、Dy 3+ Replace Lu in crystal 3+ The grids are distributed together on the same grid.

[0010] Optionally, the upper limit of x is selected from 0.0022, 0.0026, 0.0028, 0.0033, 0.0037, 0.0042, 0.0048 or 0.005; the lower limit is selected from 0.002, 0.0023, 0.0027, 0.0031, 0.0035, 0.0040, 0.0045 or 0.0048.

[0011] Optionally, the upper limit of y is selected from 0.0052, 0.0064, 0.0075, 0.0096, 0.018, 0.032, 0.044 or 0.05; the lower limit is selected from 0.005, 0.0062, 0.0074, 0.0095, 0.016, 0.030, 0.042 or 0.048.

[0012] The upper limit of x / y is selected from 0.12, 0.16, 0.25, 0.31, 0.38, 0.43, 0.46 or 0.5; the lower limit is selected from 0.1, 0.14, 0.22, 0.29, 0.36, 0.41, 0.44 or 0.48.

[0013] Optionally, Nd 3+ 、Dy 3+ 、Lu 3+ Distributed together on the same lattice, connected with 8 O atoms to form a dodecahedron, Al 3+ Sc 3+ and Ga 3+ Distributed on the same lattice site, they are connected to O atoms in four-coordinate and eight-coordinate modes.

[0014] Optionally, the absorption spectrum of the inorganic crystal material contains an absorption peak with a peak value of 448 nm.

[0015] Optionally, the absorption spectrum of the inorganic crystal material contains Nd 3+ and Dy 3+ The characteristic absorption peak of the ion is 0.596 cm at 448 nm. -1 .

[0016] Optionally, the inorganic crystal material contains four fluorescence peaks in the visible light band in the fluorescence spectrum under 448 nm pumping, and the peak values ​​of the four fluorescence peaks are respectively between 476 nm and 500 nm, between 562 and 598 nm, between 671 and 680 nm, and between 749 and 800 nm.

[0017] Preferably, the peak values ​​of the four fluorescence peaks are 496 nm, 582 nm, 677 nm and 763 nm, respectively, with the strongest peak wavelength being 496 nm.

[0018] Optionally, the resulting single crystal has at least one dimension exceeding 40 mm.

[0019] Preferably, the resulting single crystal has at least one dimension exceeding 50 mm.

[0020] Preferably, the resulting single crystal has at least one dimension exceeding 60 mm.

[0021] According to a second aspect of the present application, a method for preparing the above-mentioned inorganic crystal material is provided.

[0022] The method for preparing the inorganic crystal material described above comprises the following steps:

[0023] The polycrystalline powder of the inorganic crystal material is prepared by a high-temperature solid-phase sintering method of sesquioxides containing Nd, Dy, Lu, Al, Sc and Ga; and then the inorganic crystal material is grown by a melt pulling method.

[0024] Optionally, the following steps are included:

[0025] The raw materials Dy2O3, Nd2O3, Lu2O3, Sc2O3, Ga2O3 and Al2O3 are mixed uniformly, and pre-sintered and sintered, and the pre-sintered and sintered are repeated to obtain a polycrystalline powder of the inorganic crystal material;

[0026] The polycrystalline powder is placed in a crucible, melted in an inactive atmosphere, and grown using an intrinsic crystal polycrystalline raw material rod as a seed crystal to obtain a single crystal of the inorganic crystal material.

[0027] Optionally, in the raw material, the molar ratio of Nd, Dy, Lu, Al, Sc and Ga elements is

[0028] Nd:Dy:Lu:Al:Sc:Ga=x:y:3-xy:3:1:1

[0029] Among them, 0.002≤x≤0.005, 0.005≤y≤0.05, 0.1≤x / y≤0.5.

[0030] Optionally, the pre-sintering conditions are:

[0031] The pre-sintering temperature is 1100-1150°C, and the pre-sintering time is 24-30 hours.

[0032] Optionally, the upper limit of the pre-sintering temperature is selected from 1110°C, 1130°C, 1140°C or 1150°C; the lower limit is selected from 1100°C, 1110°C, 1120°C or 1140°C.

[0033] Optionally, the upper limit of the pre-sintering time is selected from 26h, 27h, 28h, 29h or 30h; the lower limit is selected from 24h, 25h, 26h, 27h or 28h.

[0034] Optionally, the sintering conditions are:

[0035] The sintering temperature is 1280-1350°C, and the pre-sintering time is 36-42 hours.

[0036] Optionally, the upper limit of the sintering temperature is selected from 1290°C, 1310°C, 1320°C, 1330°C, 1340°C or 1350°C; the lower limit is selected from 1280°C, 1295°C, 1310°C, 1325°C, 1335°C or 1340°C.

[0037] Optionally, the upper limit of the sintering time is selected from 37h, 38h, 39h, 40h or 42h; the lower limit is selected from 36h, 37h, 38h, 39h or 41h.

[0038] Optionally, the pre-sintering and sintering are repeated 0 to 3 times.

[0039] Specifically, the raw materials are Nd2O3, Dy2O3, Lu2O3, Al2O3, Sc2O3 and Ga2O3; the purity of each is 5N grade.

[0040] Specifically, the high temperature solid phase sintering method comprises the following steps:

[0041] a) The raw materials are accurately weighed according to the chemical reaction ratio, ground evenly, pressed into sheets, placed in a platinum crucible, placed in a sintering furnace, and slowly heated to 1100-1150°C at a heating rate not exceeding 220°C / h. After maintaining the temperature for not less than 24-30 hours, the raw materials are placed in a high-temperature sintering furnace and sintered at a constant temperature of 1280-1350°C for 36-42 hours, and the samples are taken out;

[0042] b) Repeat step a) until the X-ray powder diffraction of the sample is completely consistent with the standard card.

[0043] Optionally, the growth conditions are:

[0044] The pulling rate of the seed crystal rod is 0.45-1.55 mm / h, the cooling rate is 1-24° C. / h, and the rotation rate of the seed crystal rod is 9-15 rpm.

[0045] Preferably, the pulling rate of the seed rod is 0.5-1.5 mm / h, the cooling rate is 1-10° C. / h, and the rotation rate of the seed rod is 10-15 rpm.

[0046] Optionally, the upper limit of the pulling rate is selected from 0.6mm / h, 0.7mm / h, 0.8mm / h, 0.9mm / h, 1.0mm / h, 1.1mm / h, 1.2mm / h, 1.3mm / h, 1.4mm / h or 1.5mm / h; the lower limit is selected from 0.5mm / h, 0.6mm / h, 0.7mm / h, 0.8mm / h, 0.9mm / h, 1.0mm / h, 1.1mm / h, 1.2mm / h, 1.3mm / h or 1.4mm / h.

[0047] Optionally, the upper limit of the cooling rate is selected from 2°C / h, 3°C / h, 4°C / h, 5°C / h, 6°C / h, 7°C / h, 8°C / h, 9°C / h or 10°C / h; the lower limit is selected from 1°C / h, 2°C / h, 3°C / h, 4°C / h, 5°C / h, 6°C / h, 7°C / h, 8°C / h or 9°C / h.

[0048] Optionally, the upper limit of the rotation rate of the seed rod is selected from 11 rpm, 12 rpm, 13 rpm, 14 rpm or 15 rpm; the lower limit is selected from 10 rpm, 11 rpm, 12 rpm, 13 rpm or 14 rpm.

[0049] Optionally, after the growth is completed, the crystal is lifted out of the liquid surface and cooled to room temperature at a rate of 5 to 65° C. / h to obtain a single crystal of the crystal material.

[0050] Preferably, the temperature is lowered to room temperature at a rate of 8-25°C / h.

[0051] Optionally, after the seed rod leaves the liquid surface, the upper limit of the cooling rate is selected from 10°C / h, 15°C / h, 20°C / h or 25°C / h; the lower limit is selected from 8°C / h, 10°C / h, 15°C / h or 20°C / h.

[0052] Optionally, the polycrystalline powder is loaded into a crucible and placed in a crystal pulling furnace. The crystal pulling furnace is evacuated and filled with high-purity argon gas, and then the temperature is raised to a temperature higher than the melting point and maintained at a constant temperature to completely melt the raw materials.

[0053] Optionally, an intrinsic crystal raw material rod obtained by hot isostatic pressing is used as a seed crystal.

[0054] Specifically, the melt pulling method comprises the following steps:

[0055] The sintered polycrystalline is placed in an iridium crucible and placed in a crystal pulling furnace; the crystal pulling furnace is evacuated and filled with high-purity argon gas, and then the temperature is raised to 50°C higher than the melting point, and the temperature is kept constant for half an hour to completely melt the raw materials. The intrinsic crystal raw material rod is used as the seed crystal. During the growth process, the pulling rate of the seed crystal rod is 0.45-1.55mm / h, the cooling rate is 1-24°C / h, and the rotation rate of the seed crystal rod is 9-15r.pm; after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a rate of 5-65°C / h to obtain a size of of transparent crystals.

[0056] According to a third aspect of the present application, an application of the inorganic crystal material described above is provided.

[0057] The inorganic crystal material described above is used as a cyan laser crystal material to achieve the output of a cyan laser with a wavelength in the range of 496 nm under 448 nm pumping.

[0058] According to a fourth aspect of the present application, an all-solid-state laser is provided.

[0059] An all-solid-state laser, comprising the inorganic crystal material described above;

[0060] The all-solid-state laser achieves cyan wavelength laser output of -496nm under 448nm pumping.

[0061] Optionally, the all-solid-state laser further includes a fiber-coupled semiconductor end-face pumping module, a beam coupling system, an input mirror, a crystal material, and an output mirror;

[0062] The beam coupling system is located behind the fiber-coupled semiconductor end-face pumping module;

[0063] The input mirror is located after the beam coupling system;

[0064] The output mirror is located behind the input mirror;

[0065] The inorganic crystalline material is located between the input mirror and the output mirror.

[0066] Optionally, the pump source of the fiber-coupled semiconductor end-pump module is a 448nm LD, and an end-pump mode is adopted;

[0067] The coupling mirror of the beam coupling system is a plane mirror;

[0068] The input mirror is a concave mirror.

[0069] The beneficial effects of this application include:

[0070] 1) The inorganic crystal material provided in this application is prepared by using different concentrations of Dy 3+ 、Nd 3+ Doped Lu3Al3ScGaO 12 Through polycrystalline material synthesis, crystal growth, concentration screening and spectral performance comparison, the optimal doping concentration of Dy and Nd is obtained, which can achieve 496nm cyan band laser output and can be used in industrial fields such as mechanical cold processing and optical engraving. Only this formula can achieve ~496nm laser.

[0071] 2) The inorganic crystal material provided in this application has good optical quality and can meet the requirements of high-power all-solid-state lasers.

[0072] 3) The method for preparing the inorganic crystal material provided in the present application can grow a single crystal with a size of ф30 mm×(50-60) mm.

[0073] 4) The inorganic crystal material provided in this application is used to realize cyan band laser output, and can realize 496nm cyan band laser output under 448nm pumping. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] Figure 1 The sample S1 obtained by growth # Crystal photo.

[0075] Figure 2 It is sample S1 # Absorption spectrum of .

[0076] Figure 3 It is sample S1 # Fluorescence spectrum of .

[0077] Figure 4 YesNd 3+ -Dy 3+ Schematic diagram of the energy transfer mechanism.

[0078] Figure 5 is a schematic diagram of the laser experimental setup in which the sample is applied.

[0079] List of parts and reference numerals:

[0080] Figure 5 In the figure, 1. Fiber-coupled semiconductor end-face pump module; 2. Beam coupling system prism; 3. Beam coupling system prism; 4. Input mirror; 5. Crystal sample; 6. Semiconductor saturable absorber (SA); 7. Output mirror. DETAILED DESCRIPTION

[0081] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0082] Unless otherwise specified, the raw materials and reagents used in this application were purchased from commercial sources and used directly without treatment. The instruments and equipment used adopted the schemes and parameters recommended by the manufacturers.

[0083] In the embodiment, the instrument used for crystal pulling growth is a JGD-600 medium frequency pulling furnace produced by the 26th Institute of China Electronics Technology Group Corporation. The computer controls the heating power, heating and cooling speed, and pulling speed, and the crucible used is an iridium crucible of Ф80mm×60mm.

[0084] In the embodiment, the raw materials used are Dy2O3, Nd2O3, Lu2O3, Sc2O3, Ga2O3 and Al2O3 with a purity of 99.999%.

[0085] In the examples, the absorption spectrum of the crystal sample was measured on a Lambda950 absorption spectrometer produced by Pekin-Elmer; the fluorescence spectrum under 448 nm pumping was measured on a FLS980 fluorescence spectrometer produced by Edinburgh, UK.

[0086] Example 1 Polycrystalline material preparation and crystal growth

[0087] According to the ratio in the chemical formula (Nd:Dy:Lu:Al:Sc:Ga=x:y:3-xy:3:1:1), 5N grade Dy2O3, Nd2O3, Lu2O3, Sc2O3, Ga2O3 and Al2O3 are accurately weighed and poured into a polytetrafluoroethylene tank, zirconium balls of appropriate proportion and size and an appropriate amount of alcohol are added, and the mixture is evenly mixed in a mixer. The raw materials are pressed into sheets, put into a corundum crucible, placed in an ordinary sintering furnace, and slowly heated to the pre-sintering temperature at a certain rate, and maintained for a period of time; then placed in a high-temperature sintering furnace and sintered at a constant temperature for a period of time at the sintering temperature, and the sample is taken out; the above pre-sintering and sintering steps are repeated until the X-ray powder diffraction is completely consistent with the XRD standard JCPDS card of the crystal, and a polycrystalline sample of the crystal material is obtained.

[0088] The polycrystalline raw material obtained by sintering is placed in an iridium crucible of Ø80mm×60mm. To avoid oxidation of the iridium crucible, the air in the furnace is first evacuated to make the pressure in the furnace reach minus 0.25Pa, and then high-purity argon is filled to make the pressure reach 0.14MPa. Then the temperature is raised to 50°C higher than the melting point, and the temperature is kept constant for half an hour to completely melt the raw material. The intrinsic crystal polycrystalline raw material rod obtained by hot isostatic pressing is used as the seed crystal. During the growth process, the pulling rate, cooling rate, and rotation rate of the seed crystal rod are set; after the growth is completed, the crystal is lifted from the liquid surface and cooled to room temperature at a certain rate to obtain a transparent single crystal sample of the crystal material.

[0089] The preparation operation is the same as above, except that the values ​​of x, y, x / y are changed, as well as the polycrystalline material synthesis and crystal growth conditions. The relationship between the sample numbers obtained, the pre-sintering conditions and sintering conditions during the high-temperature sintering process, the pulling rate of the seed crystal rod during the Czochralski method crystal growth process, the cooling rate, the rotation rate of the seed crystal rod, the cooling rate of the crystal rod leaving the liquid surface to room temperature after the growth is completed, and the size of the obtained samples is shown in Table 1.

[0090] Table 1

[0091]

[0092] Among them, single crystal sample S1 # The component ratio is x = 0.004, y = 0.01, x / y = 0.4, and the crystal photo obtained is as follows Figure 1 As shown, the single crystal sample S1# has a crystal size of 31 mm in diameter and 65 mm in length.

[0093] Single crystal sample S2 # The component ratio is x=0.008, y=0.01, x / y=0.8.

[0094] Single crystal sample S3 # The component ratio is x=0.0025, y=0.1, x / y=0.025.

[0095] Single crystal sample S4 # The component ratio is x=0.0045, y=0.05, x / y=0.09.

[0096] Single crystal sample S5 # The component ratio is x=0.001, y=0.05, x / y=0.02.

[0097] Example 2 Spectral performance measurement of the sample obtained

[0098] From the bulk crystal sample S1 # ~S5 # In the process, several sizes of 10.0×10.0×1.0mm are processed respectively. 3 The spectral performance of the crystal slices was tested and studied.

[0099] Taking crystal sample S1# as a typical example, its absorption spectrum is as follows Figure 2 As shown in the figure, the absorption spectrum of the sample shows that Dy 3+ and Nd 3+ The characteristic absorption peak of Dy 3+ There are 12 main characteristic absorption peaks, which are located at 327nm, 353nm, 367nm, 387nm, 448nm (absorption coefficient is 0.596cm -1 ), 479nm, 752nm, 804nm, 905nm, 1074nm, 1292nm, 1689nm, corresponding to Dy 3+ exist 6 H 15 / 2 The ground state energy level of the particle 6 P 3 / 2 + 4 I 9 / 2 , 6 P 7 / 2 + 6 I 11 / 2 , 6 P 5 / 2 + 4 M 19 / 2 , 4 F 7 / 2 + 4 I 13 / 2 , 4 I 15 / 2 , 4 F 9 / 2 , 6 F 3 / 2 ,6 F 5 / 2 , 6 F 7 / 2 , 6 F 9 / 2 + 6 H 7 / 2 , 6 F 11 / 2 + 6 H 9 / 2 and 6 H 11 / 2 In addition, Nd appears in the 500-540nm, 560-600nm and 720-750nm bands. 3+ The characteristic absorption bands of Nd 3+ of 4 I 9 / 2 → 2 K 13 / 2 , 4 I 9 / 2 → 5 G 5 / 2 + 2 H 11 / 2 and 4 I 9 / 2 → 4 G 11 / 2 + 2 P 1 / 2 Energy level transition. Nd has a good sensitization effect on Dy, which enhances the crystal's absorption of pump light. In addition, since the former has a relatively large absorption intensity and a relatively wide absorption band, it matches the commercial blue light semiconductor pump source, making several sample crystals very suitable for laser experiments using commercial 448nm blue light diode pumping.

[0100] Taking crystal sample S1# as a typical example, the room temperature fluorescence spectrum under 448nm pumping is shown in Figure 3 As shown in the figure, the sample has four main fluorescence peaks in the visible light band, with peaks at 496nm, 582nm, 677nm and 763nm, respectively, and the strongest peak wavelength is 496nm. In the single crystal sample S1#, effective Nd 3+ -Dy 3+ The energy transfer mechanism diagram is as follows Figure 4 As shown. 3+ Ionic 4 F 9 / 2 Energy Level and Nd 3+ Ionic 2 G 9 / 2 The energy levels are close, and the energy will be transferred from Nd 3+ Ion to Dy 3+The ion transfer process is the quasi-resonance energy transfer ET1 process. 3+ ion 4 F 9 / 2 The fluorescence lifetime of the energy level indicates that the energy transfer efficiency of the ET1 process is 4.94%.

[0101] The obtained crystal sample S2 # ~S5 # The spectral performance was measured as described above and it was found that:

[0102] S2 # Due to the high Nd doping concentration in the sample, the fluorescence emission of Nd dominates and masks the fluorescence emission of Dy.

[0103] S3 # Due to the high Dy doping concentration in the sample, the fluorescence intensity of the crystal in the cyan band is greatly reduced, while the fluorescence emission in other visible bands such as yellow light is very strong, which is not conducive to the realization of cyan band laser.

[0104] S4 # The sample suffers from fluorescence quenching due to the mismatch of Nd-Dy ion concentration ratio, and cannot achieve effective cyan band fluorescence emission.

[0105] S5 # Since the concentration of Nd ions in the sample is too low, effective Nd-Dy sensitization cannot be achieved and the absorption in the blue light band is very weak, which is not conducive to the realization of laser.

[0106] Example 3 Application of the obtained sample in a laser device

[0107] Take sample S1 respectively # ~S5 # The size of the crystal is 3mm×3mm×(5~10)mm, and the two ends of the crystal are polished to 3mm×3mm, which is used in laser devices. Figure 5 As shown, it includes a fiber-coupled semiconductor end-face pumping module 1, a beam coupling system, an input mirror 4, a crystal sample 5, a semiconductor saturable absorber (SA) 6, and an output mirror 7; the beam coupling system (including a beam coupling system prism 2 and a beam coupling system prism 3) is located behind the fiber-coupled semiconductor end-face pumping module 1; the input mirror 4 is located behind the beam coupling system; the output mirror 7 is located behind the input mirror 4; the crystal sample 5 is located between the input mirror 4 and the output mirror 7, and the semiconductor saturable absorber (SA) 6 is located between the crystal sample 5 and the output mirror 7.

[0108] The crystal sample was placed in a water-sealed copper tube. The pump source used was a 448nm blue light LD, using end pump mode. The input mirror was a concave mirror with a diameter of 200mm, which was highly transparent at 448nm and highly reflective at 490-510nm. The coupling mirror was a plane mirror, and the transmittance at the laser wavelength of 496nm was 0.5%, 1%, 2%, 3% and 4%. The laser spectrum was measured using a laser wavelength meter, model 821B-IR, Bristol, and the laser power was measured using a power meter, model LPE-1B.

[0109] The results show that the application of sample S1 # The laser device can achieve 496nm cyan laser output.

[0110] Replace the above samples with S2 # ~S5 # , and applied them to laser devices, the results showed that no effective ~496nm cyan laser output was achieved.

[0111] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An inorganic crystalline material, characterized in that: The chemical formula of the inorganic crystalline material is Nd x Dy y Lu 3-x- y Al3ScGaO 12 ; Among them, 0.002≤x≤0.005, 0.005≤y≤0.05, 0.1≤x / y≤0.5; Nd 3+ 、Dy 3+ Replace Lu in crystal 3+ The grids are distributed together on the same grid.

2. The inorganic crystal material according to claim 1, characterized in that: Nd 3+ 、Dy 3+ 、Lu 3+ Distributed together on the same lattice, connected with 8 O atoms to form a dodecahedron, Al 3+ Sc 3+ and Ga 3+ They are distributed on the same lattice site and connected to O atoms in four-coordinate and eight-coordinate modes.

3. The inorganic crystal material according to claim 1, characterized in that: The absorption spectrum of the inorganic crystal material contains an absorption peak with a peak value of 448nm; Preferably, the absorption spectrum of the inorganic crystal material contains both Nd 3+ and Dy 3+ The characteristic absorption peak of the ion is 0.596 cm at 448 nm. -1 ; Preferably, the inorganic crystal material has four fluorescence peaks in the visible light band in the fluorescence spectrum under 448nm pumping, and the peak values ​​of the four fluorescence peaks are respectively between 476nm and 500nm, between 562 and 598nm, between 671 and 680nm, and between 749 and 800nm; Preferably, the peak values ​​of the four fluorescence peaks are 496nm, 582nm, 677nm and 763nm, respectively, wherein the strongest peak wavelength is 496nm; Preferably, the obtained single crystal has at least one dimension exceeding 40 mm; Preferably, the resulting single crystal has at least one dimension exceeding 50 mm.

4. The method for preparing the inorganic crystal material according to any one of claims 1 to 3, characterized in that: The following steps are involved: The polycrystalline powder of the inorganic crystal material is prepared by a high-temperature solid-phase sintering method of sesquioxides containing Nd, Dy, Lu, Al, Sc and Ga; and then the inorganic crystal material is grown by a melt pulling method.

5. The preparation method according to claim 4, characterized in that: The following steps are involved: The raw materials Dy2O3, Nd2O3, Lu2O3, Sc2O3, Ga2O3 and Al2O3 are mixed uniformly, and pre-sintered and sintered, and the pre-sintered and sintered are repeated to obtain a polycrystalline powder of the inorganic crystal material; The polycrystalline powder is placed in a crucible, melted in an inactive atmosphere, and grown using an intrinsic crystal polycrystalline raw material rod as a seed crystal to obtain a single crystal of the inorganic crystal material.

6. The preparation method according to claim 5, characterized in that: In the raw materials, the molar ratio of Nd, Dy, Lu, Al, Sc and Ga elements is Nd:Dy:Lu:Al:Sc:Ga=x:y:3-xy:3:1:1 Among them, 0.002≤x≤0.005, 0.005≤y≤0.05, 0.1≤x / y≤0.

5.

7. The preparation method according to claim 5, characterized in that: The pre-sintering conditions are: The pre-sintering temperature is 1100-1150°C and the pre-sintering time is 24-30h; Preferably, the sintering conditions are: The sintering temperature is 1280-1350°C, and the pre-sintering time is 36-42h; Preferably, the pre-sintering and sintering are repeated 0 to 3 times.

8. The preparation method according to claim 5, characterized in that: The growth conditions are: The pulling rate of the seed crystal rod is 0.45-1.55 mm / h, the cooling rate is 1-24°C / h, and the rotation rate of the seed crystal rod is 9-15 rpm; Preferably, after the growth is completed, the crystal is lifted out of the liquid surface and cooled to room temperature at a rate of 5 to 65° C. / h to obtain a single crystal of the crystalline material.

9. The inorganic crystal material according to any one of claims 1 to 3 is used as a cyan laser crystal material to achieve the output of cyan laser with a wavelength in the range of 496 nm under 448 nm pumping.

10. An all-solid-state laser, characterized in that: An inorganic crystal material comprising any one of claims 1 to 3; The all-solid-state laser achieves a cyan laser output of ~496nm under 448nm pumping; Preferably, the all-solid-state laser further comprises a fiber-coupled semiconductor end-face pumping module, a beam coupling system, an input mirror, a crystal material, and an output mirror; The beam coupling system is located behind the fiber-coupled semiconductor end-face pumping module; The input mirror is located after the beam coupling system; The output mirror is located behind the input mirror; The inorganic crystalline material is located between the input mirror and the output mirror.

Citation Information

Patent Citations

  • Preparation method of composite laser crystal in garnet structure

    CN102560666A

  • Method for growing specific-size rare-earth-doped gallium-containing garnetite series crystal by edge-defined process

    CN104962994A

  • Efficient near-infrared radiation-resistant laser crystal and preparation method thereof

    CN110607559A

  • Preparation method and application of composite ceramic material

    CN114773048A

  • Garnet crystal waveguide having amplifying action

    JP1995281040A